Environmental Communication for Children Media, Young Audiences, and the More-Than-Human World - Hawley, Erin. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"This book will occupy a distinct niche in the growing and increasingly influential field of 'eco-media studies'. It brings children's media to the forefront of our attention precisely at the moment when children's voices are becoming increasingly prominent in conversations about environmental crisis." - John Parham, Professor of Environmental Humanities at the University of Worcester, UK. This book explores the nexus between children, media, and nature during a time of planetary crisis marked by climate change, biodiversity loss, and environmental degradation. In this time of planetary emergency, children have become an increasingly visible part of conversations about the human/nature relationship - they have also become an important market for environmentally-themed media content. Indeed, recent years have seen a proliferation of environmental texts, products, and narratives for young people: children are recognised and addressed as audiences for environmental content across a range of media including news, films, television programs, magazines, videogames, and transmedia franchises. Through analysis of a range of case studies, this book examines the construction of children as green audiences, the intersection between media and environmental literacies, and the mainstreaming of children's voices in environmental communication. The book will appeal to readers with an interest in children's media and the industry imperatives that shape the production of children's culture as well as to students, scholars, and practitioners in the field of environmental communication. Erin Hawley is a Lecturer in Communication at Deakin University, Australia.
Chapter 1 - The child/nature relationship -- Chapter 2 - Environmental and media literacies -- Chapter 3 - Covering the environment in children's news -- Chapter 4 - The greening of children's television -- Chapter 5 - Nature on screen in children's film -- Chapter 6 - Young explorers in virtual worlds -- Chapter 7 - The mainstreaming of children's voices in environmental communication.
Keywords: Communication in the environmental sciences; Youth-Social life and customs; Education; Children; Environmental Communication; Youth Culture; Childhood Education